Mermaids in the Backyard - Hapka, Cathy; Castelao, Patricia (New York : Random House, 2013)
When her family moves from Chicago to an island in South Carolina, Lindy is sure she will be unhappy until she makes a surprising discovery in the backyard of their beach house.
Keywords: Mermaids -- Juvenile fiction; Ocean -- Juvenile fiction; Moving, Household -- Juvenile fiction; Mermaids -- Fiction; Ocean -- Fiction; Moving, Household -- Fiction